Analysis of microbial diversity in pesticide-contaminated soil: A study of culturable microorganisms - Lamuka, Andre Putra; Aliwu, Putri Liani (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Pesticide contamination of soil often leads to significant alterations in the structure and diversity of microbial communities, potentially affecting overall ecosystem function. Understanding these changes is crucial for assessing the ecological impact of pesticide use in agricultural areas. This study analyzes microbial diversity in pesticide-contaminated soil using the Shannon-Wiener diversity index to evaluate the effects of pesticide exposure on microbial populations. Methods: A descriptive quantitative approach was used, incorporating the Total Plate Count (TPC) test and Shannon-Wiener Index analysis. The numerical data included the number of microbial individuals (bacteria and fungi) and the relative proportion of each group. Soil samples were purposively collected from three points in a pesticide-contaminated tomato farming area in Dunggala Village, Gorontalo Regency. Findings: The microbial community detected in the contaminated soil consisted of bacteria (2.5×10⁴ CFU/ml) and fungi (1.35×10³ CFU/ml). The Shannon-Wiener index value was 0.202, indicating low microbial diversity. This suggests that pesticide contamination negatively impacts microbial richness and evenness in the soil. Conclusion: Pesticide contamination significantly reduces microbial diversity, as reflected in the low Shannon-Wiener index value. This decline in microbial richness and evenness highlights the potential ecological consequences of pesticide use in agriculture. To mitigate these negative effects, implementing sustainable pest management practices, such as the use of biopesticides, is recommended. Novelty/Originality of this article: This study provides quantitative evidence of the decline in microbial diversity in pesticide-contaminated soil using the Shannon-Wiener index. By focusing on microbial community changes in a specific agricultural setting, the findings contribute to a better understanding of the ecological impacts of pesticide use and emphasize the need for sustainable pest management strategies.